Empowering the Independence of Partworld Women in the Use of the DPP Solution Application as a Preventive Measure for Post Partum Blues - Solikhah, Fitriana; Tyas, Maria Diah Ciptaning (Tarqabin Nusantara Group, 2023)
Postpartum blues is a mild postpartum stress syndrome experienced by mothers within 3-10 days. Postpartum blues has symptoms such as excessive sadness, sudden crying, irritability, difficulty sleeping, headaches, and a tendency to blame yourself. Postpartum blues causes mothers to become passive and ignore their babies as well as hormonal imbalances due to anxiety and stress. Mothers experiencing excessive stress have an impact on decreasing interest and interest in babies and the ability to care for their babies properly, not being enthusiastic about breastfeeding so that the health and development of the baby is not optimal. The novelty of this community service activity can provide education regarding the prevention of postpartum depression by using an application. This service activity was attended by posyandu cadres, couples of childbearing age (PUS), pregnant women and postpartum mothers. The purpose of this service activity is to increase public understanding of the prevention of postpartum depression, to be skilled at self-detection and its citizens about postpartum depression. The target of this activity is 30 people. The activity method is carried out twice by giving a pre test, lecture and followed by a post test by filling out a questionnaire. The evaluation was carried out with cadres by conducting interviews on their understanding of prevention of postpartum depression. The results achieved in this activity are that the community gains knowledge about postpartum depression.